Solvent-Free Condensation of Phenols with Aldehydes and Amides Using 3-Methyl-1-sulfonic Acid Imidazolium Chloride - Moosavi-Zare, Ahmad Reza; Zolfigol, Mohammad Ali; Daraei, Masoume (Synlett, 2014)
One-pot, three-component condensation of phenols, aromatic aldehydes, and amides in the presence of 3-methyl-1-sulfonic acid imidazolium chloride {[Msim]Cl} as ionic liquid and catalyst under solvent-free condition to prepare a new category of compounds, namely amido-alkyl-phenols has been described. In the presented work, all products have been reported for the first time.
Keywords: amidoalkyl phenol; ionic liquid; sulfonic acid functionalized imidazolium salts; SAFIS; phenol; aldehyde; solvent-free